Impedance sensitive STATCOM control for systems supported by renewable generation - Rose, Christopher James; Sumner, Mark; Thomas, David W.P.; Christopher, Edward (2014)
Reactive power control is known to be an effective means of controlling voltage; however, for optimal performance, the system reactance must be known. Power systems with high re-newable energy penetration have been known to have voltage stability issues. To further complicate this issue, distributed renewable sources are likely to have an effect on the local sys-tem impedance. As a result, connection and disconnection of such sources is likely to result in significant changes in system impedance. In this paper, impedance estimation is used to dy-namically tune the controllers of a STATCOM so that consis-tent dynamic performance may be obtained. The method has been verified through simulation and through laboratory-based experimentation